(untitled) (مجلة المنصور, 2022)
In this paper, some theorems are modified to ensure the existence and uniqueness of the solution for the Quasi – Lyapunov operator equation. Also, the range of the Quasi – Lyapunov equation is studied. As well as, the nature of the solution for the Quasi – Lyapunov operator equation is studied for special types of operators.